The Effect Discovery Learning Model Using 3D Interactive Media On Students' Learning Outcomes At SMPN 4 Payakumbuh - Hanifa, Azkia; Oktavia, Rani; Yanto, Febri; Diliarosta, Skunda; Sazaliana, Ade (SEMESTA: Journal of Science Education and Teaching, 2026)
Through the use of interactive 3D media, this study aims to examine how the Discovery learning model affects seventh-grade students' academic achievement. This research is motivated by the insufficient diversity of learning media utilized in the classroom. A nonequivalent control group design is applied in the research approach, which is quasi-experimental. The experimental class will implement the Discovery Learning model utilizing 3D media, while the control group will use the same model without the support of 3D media. The employed sample method is purposive sampling. A student response questionnaire and an exam with twenty-four objective questions make up the research tools. Parametric tests, particularly t-tests, were used for data analysis, along with tests for normality and homogeneity. Results of the student response questionnaire regarding with the use of interactive 3D media, the Discovery Learning model achieved a 95% success rate, which is considered excellent. A total implementation rate of 97.94% was determined to be indicative of successful implementation of the Discovery Learning Model accompanied by interactive 3D media, according to the observation data. The t-value of 2.18 is higher than the t-table value of 2.00, leading to the rejection of H₀ in the hypothesis test. This indicates that student learning outcomes in grade VII of senior high school are significantly influenced by the Discovery Learning Model supported by 3D interactive media covering material about the Earth and the solar system.